Hematological Effects Following Ingestion of Allium cepa (Onion), Allium sativum Garlic and Treatment with Iodine in Albino Wistar Rats - Uduak I., Aletan (Pakistan Journal of Nutrition, 2014)
This study was aimed at assessing the extent to which ingestion of Allium cepa (onion) Allium sativum (garlic) and treatment with iodine affect haematological parameters of albino Wistar rats. The effect on total hemoglobin, hematocrit (PCV%), red blood cells (RBC) and mean cell hemoglobin concentration (MCHC) were carried out. Oral administration of onion and garlic extract led to a dose dependent decrease in the total haemoglobin level of normal rats which was not statistically significant (p